Optimum thermal performance of green walls systems and design requirements against heat transfer of conventional external walls of low-rise concrete buildings in hot regions - Khabaz, Amjad (Elsevıer)
This paper presents a study on how the thermal performance of conventional external walls of concrete building could be improved against heat transfer in hot regions. 45 buildings were visited to observe the heat transfer from the warmer side of the external wall to the cooler side. The measurements showed that the conventional walls are insufficient because of high indoor temperatures. This study introduced three environmentally friendly scenarios to enhance the efficiency of the concrete wall against heat transfer. In the first scenario, a continuous air layer was added at the middle of the wall to form an aired-concrete wall. In the second scenario, a living green layer was added on the exterior side of the wall to form a living-concrete wall. The third scenario merged the previous two insights to form a living-aired-concrete wall. Thermal models were prepared to conduct thermal analysis. The results showed that the air layer deactivates the work of thermal bridges and improves the thermal resistance of the wall 5 to 15 times. In the aired-concrete wall, the results showed that the minimum depth of the air layer should be at least 6 cm, to secure a convenient indoor environment with indoor temperature not more than 25 degrees C. Furthermore, the results showed that adding only an outdoor living green layer to the conventional wall is insufficient in all thermal zones of hot regions. Finally, the best thermal performance against heat transfer was found in the living-aired-concrete wall using outdoor Perennials plants and 5 cm middle air layer.
Keywords: Green wall; Conventional concrete wall; Thermal conductivity; Thermal analysis; Conductivity heat transfer